2012
DOI: 10.1111/j.1365-2648.2011.05922.x
|View full text |Cite
|
Sign up to set email alerts
|

Using the Theory of Planned Behaviour to predict nurses’ intention to integrate research evidence into clinical decision‐making

Abstract: The present study supports the use of an extended psychosocial theory for identifying the determinants of nurses' intention to integrate research evidence into their clinical decision-making. Interventions that focus on increasing nurses' perceptions that using research is their responsibility for ensuring good patient care and providing a supportive environment could promote an evidence-based nursing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 40 publications
2
30
1
3
Order By: Relevance
“…The significant relationship between past behavior and intention was observed in previous studies (e.g. Côté, Gagnon, Houme, Abdeljelil, & Gagnon, 2012), and the relationship between some gender characteristics and research intention was found in the study by Wright and Holttum (2012).…”
Section: Research Focusessupporting
confidence: 53%
See 1 more Smart Citation
“…The significant relationship between past behavior and intention was observed in previous studies (e.g. Côté, Gagnon, Houme, Abdeljelil, & Gagnon, 2012), and the relationship between some gender characteristics and research intention was found in the study by Wright and Holttum (2012).…”
Section: Research Focusessupporting
confidence: 53%
“…All the more, "intention" is believed to be a proxy of or strongly related to actual behaviors in previous studies in various fields (e.g. Rose, Zimmermann, Pfeifer, Unterbrink, & Bauer, 2010;Côté, Gagnon, Houme, Abdeljelil, & Gagnon, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The significant relationship between past behavior and intention was observed in previous studies (e.g. Côté, Gagnon, Houme, Abdeljelil, & Gagnon, 2012), and the relationship between some gender characteristics and research intention was found in the study by Wright and Holttum (2012).…”
Section: Research Focusessupporting
confidence: 51%
“…For instance, France, France, and Himawan (2007) studied the intention to re-donate blood among experienced blood donors and found that the Planned Behavior Theory variables accounted for 65% of variances in intention. Côté et al (2012) used Planned Behavior Theory constructs to predict intention of nurse to integrate research evidence into clinical decision making and could detect up to 70% of intention variances explained by moral norm, normative beliefs, perceived behavioral control, and past behaviors. We [the authors of this present study] believed that the lower detected explained variances in our study was due to our specifically trimmed framework that tapped only into few key variables.…”
Section: Conclusion Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation